The natural projection approach to production and uncertainty - Pascal Stiefenhofer (Kiel Institute for the World Economy (IfW), 2011)
The paper generalizes the natural projection approach introduced by Balasko (1988) for the study of the qualitative equilibrium structure of exchange economies to a two period private ownership production model with uncertainty. It shows that long run equilibrium properties of the production model are those of the pure exchange economy with production adjusted demand functions. Associated with every long run equilibrium there exist a finite, odd number of short run equilibria.
Keywords: D62; D52; D53; 330; existence of equilibrium; uncertainty; production; Gleichgewicht; Allgemeines Gleichgewicht; Theorie